AI as a Learning Partner: Exploring Ethical Awareness of Engineering Students - Md., Ashrafuzzaman; Sanjida Sumaia, Mimmo; Md. Mohaimenul, Islam Noyon; Md. Rabbi, Khan (INTI International University, 2025)
In recent years, Artificial Intelligence, particularly generative AI tools, has become increasingly integrated into the daily learning experience of engineering students. These tools provide excellent support for coding, designing, and problem-solving activities, like learning facilitators. However, this tendency of using AI raises important ethical questions: Are students fully aware of when and how the use of AI may cross ethical boundaries, such as plagiarism or over-reliance on technology? This study investigates the ethical awareness of undergraduate engineering students regarding the use of AI tools and examines the challenges they encounter in balancing AI assistance with academic integrity. Using a mixed-methods approach, data were collected from 103 undergraduate engineering students and 10 faculty members through surveys and interviews. Quantitative data were analyzed using descriptive statistics and inferential tests, including the Mann-Whitney U test, to examine differences in students’ verification behaviors based on their awareness levels, while qualitative data were analyzed thematically. The findings showed that while students find AI helpful, many lack understanding of its ethical boundaries. Teachers emphasize the importance of incorporating ethical awareness-related training and establishing clear guidelines within the curriculum to address existing gaps. This study suggests that with appropriate policies and quality education, AI can be used ethically to enhance learning without compromising academic integrity.